Assessment of targeted non-intentionally added substances in cosmetics in contact with plastic packagings. Analytical and toxicological aspects. (June 2019) - Murat, Pauline; Ferret, Pierre-Jacques; Coslédan, Sylvie; Simon, Valérie
Abstract: Container-content interactions are common in the food and pharmaceutical industries. However, these studies are more complicated in the cosmetic industry, and it is necessary to ensure consumer safety. The objective of this work was to develop a strategy for the toxicological evaluation of leachables for cosmetic packagings. Eleven common plastic packagings were selected to evaluate interactions with 5 simulants (acidic, alkaline and neutral water, 30% and 96% ethanol) chosen to mimic cosmetics behavior. A GC-MS method was developed to screen for 12 non-intentionally added substances of particular concern: 10 phthalates, bisphenol A and distearyl thiodipropionate (European Pharmacopoeia plastic additive 17). Results were analyzed using a toxicological procedure established for this study. Some phthalates and bisphenol A were detected in several samples, but only one contaminant, diisobutyl phthalate (DiBP), was found to be above the set concentration threshold. Using toxicological data, this concentration was found to be safe for users. 96% ethanol appeared to be the strongest simulant in term of extraction, with a maximum concentration of 491 μg/L for DiBP in a 100% styrene-acrylonitrile copolymer packaging. In water simulants, less contaminants were extracted, with concentrations under 20 μg/L. Graphical abstract: Image 1 Highlights: A pragmatic approach for a toxicological evaluation of cosmetic packaging leachables is proposed. Eleven plastic packagings were studied using five simulants to mimic interactions between container and content. Twelves NIAS of concern (ten phthalates, bisphenol A and distearyl thiodipropionate) were screened by GC/MS. DiBP was the only compound detected above the selected concentration threshold in one packaging. The derived calculated exposure estimated using SED was not of safety concern.